Metodologias ativas no ensino de biologia: a produção de jogos didáticos como estratégia ao letramento científico - Barbosa, Monaliza Silva Amorim (2020)
Nowadays, the active methodologies application is valuable to transform educational practices to facilitate the learning process. According to the official documents (PCN‟s, LDB, BNCC) that guide the teaching process, concerning Science and Biology teaching especific objectives: to promote teaching-learning situations where students have the opportunity to become protagonists in their own educational process; promote knowledge production to contribute to comprehend the world and its changes. At this point, the educational games application, as an active methodologies‟ tool which enables critical and creative teaching strengthening, to promote the scientific knowledge and improvements in the results of knowledge‟s comprehension construction, concerning the student in the process‟ centre. This paper purposes to analyze the pedagogical efficiency by educational games‟ application, as an active methodology, to promote literacy in Biology‟s teaching-learning in basic education. The research is a quali-quantitative that aims to guide by action research, which has investigated on the pedagogical games‟ contribution as a didactic tool in the learning promotion and in the improvement of the scientific literacy students levels in the third grade. High school grade. Data has been collected through questionnaires, participant observation, focus group and record in field diaries and treated based on content analysis. The activities‟ development and games‟ application to develop high school Biology content. Research has demonstrated that the importance to apply educational games is relevant to scientific literacy levels improving, to be considered one of most building knowledge effective means. The production of a didactic game process. Futhermore, in the knowledge construction, motivation and the cognition development by offering meaningful learning by approaching content in a contextualized and funny way. Moreover, to contribute to improve performance in the classroom and to a reflective and critical educational process in the educational practice. As a result, concerning the activities made, a Biological Sciences Educational Games has been produced, consisting of educational games and an academic portfolio. The portfolio contains the pedagogical path that involved this research, as well as the theoretical approaches that supported the production of games. Such products constituted the school's pedagogical collection, and will be available to other Science and Biology teachers in basic education through the national repository.